Functional Conducting Polymers in the Application of SPR Biosensors. (5th July 2012) - Janmanee, Rapiphun; Chuekachang, Sopis; Sriwichai, Saengrawee; Baba, Akira; Phanichphant, Sukon
Abstract : In recent years, conducting polymers have emerged as one of the most promising transducers for both chemical, sensors and biosensors owing to their unique electrical, electrochemical and optical properties that can be used to convert chemical information or biointeractions into electrical or optical signals, which can easily be detected by modern techniques. Different approaches to the application of conducting polymers in chemo- or biosensing applications have been extensively studied. In order to enhance the application of conducting polymers into the area of biosensors, one approach is to introduce functional groups, including carboxylic acid, amine, sulfonate, or thiol groups, into the conducting polymer chain and to form a so-called "self-doped" or by doping with negatively charged polyelectrolytes. The functional conducting polymers have been successfully utilized to immobilize enzymes for construction of biosensors. Recently, the combination of SPR and electrochemical, known as electrochemical-surface plasmon resonance (EC-SPR), spectroscopy, has been used for in situ investigation of optical and electrical properties of conducting polymer films. Moreover, EC-SPR spectroscopy has been applied for monitoring the interaction between biomolecules and electropolymerized conjugated polymer films in biosensor and immunosensor applications. In this paper, recent development and applications on EC-SPR in biosensors will be reviewed.